Data Management, Analytics and Innovation Proceedings of ICDMAI 2018, Volume 2 - Balas, Valentina Emilia; Sharma, Neha.; Chakrabarti, Amlan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The volume on Data Management, Analytics and Innovations presents the latest high-quality technical contributions and research results in the areas of data management and smart computing, big data management, artificial intelligence and data analytics along with advances in network technologies. It deals with the state-of-the-art topics and provides challenges and solutions for future development. Original, unpublished research work highlighting specific research domains from all viewpoints are contributed from scientists throughout the globe. This volume is mainly designed for professional audience, composed of researchers and practitioners in academia and industry.
An empirical study of website personalization effect on users intention to revisit ecommerce website through cognitive and hedonic experience -- Hierarchical Summarization of Text Documents using Topic Modeling and Formal Concept Analysis -- Green Information and Communication Technology Techniques in Higher Technical Education Institutions for Future Sustainability -- Comparative Study of Different Similarity Metrics in Highly Sparse Rating Dataset -- Multi-Document Summarization & Opinion Mining Using Stack Decoder Method and Neural Networks -- Data mining technology with fuzzy logic, neural networks and machine learning for agriculture -- 6-Tier Design Framework for Smart Solution as a Service (SSaaS) using Big Data.
Keywords: Telecommunication; Big data; Artificial intelligence -- Data processing; Artificial intelligence; Communications Engineering, Networks; Big Data; Data Science; Artificial Intelligence